Using pens as an incentive for trial recruitment of older adults: An embedded randomised controlled trial - Whiteside, Katie (F1000Res, 2019)
Background: Meeting recruitment targets for randomised controlled trials is challenging.  This trial evaluated the effectiveness of including a pen within the trial invitation pack on the recruitment of older adults into a randomised controlled trial. Methods: This trial was embedded within the Occupational Therapist Intervention Study, a falls-prevention randomised controlled trial.  Potential participants (n = 1862), who were posted an invitation pack from two General Practitioner practices, were randomised to either not receive a pen (n = 1295) or receive a pen (n = 648) with their invitation pack, using a 2:1 ratio.  The primary outcome was the likelihood of being randomised, and therefore fully recruited, to the host trial.  To be randomised to the host trial, participants had to: return a consent form and screening form; be eligible on their screening form; and return a baseline questionnaire and a monthly falls calendar.  Secondary outcomes were: the likelihood of returning (and time to return) a screening form; being eligible for the host trial; and remaining in the trial for at least 3 months. Results: The likelihood of being randomised to the host trial did not differ between the pen group (4.5%) and no pen group (4.3%; odds ratio 1.04; 95% confidence interval: 0.65 to 1.67; p = 0.86).  There were marginal differences in secondary outcomes in favour of the pen group, particularly in screening form return rates, though these differences were not statistically significant. Conclusion: Pens may not be an effective incentive for the recruitment of older adults into randomised controlled trials, though future trials are required. Registration: ISRCTN22202133; SWAT 37.